Akulturasi Budaya Bali-Tionghoa pada Interior TITD Ling Sii Miao Tanah Kilap, Denpasar - Santoso, Gunawan Nyoto; Setiawan, Andereas Pandu; Nilasari, Poppy Firtatwentyna (Intra, 2017)
TITD Ling Sii Miao Tanah Kilap is a unique temple in Denpasar due to the acculturation between Chinese and Balinese culture in its building design. The values of Tri Dharma along with Balinese culture that are commonly sensed by visitors are unconsciously triggered by the design of this temple. The history, art and religion that ran along together from the olden days till today cannot be separated from one another as every detail of the building design contains historical stories, art and Tri Dharma values along with Balinese culture.This research aims to study and understand every detail of the temple’s building design, from its architecture to its interior design, in regards to the acculturation of Chinese and Balinese culture that have taken place.